Fretting fatigue and wear behaviour of timetal 834 - Garg R.; Sudhakar Rao G.; Bhartia V.; Singh V. (My University, 2025)
Fretting fatigue behaviour of solution treated and aged near a-titanium alloy Timetal 834 was investigated at a constant stress amplitude of ±800 MPa, and different contact stresses of 50, 63, and 75 MPa at cyclic frequency of 0.1 Hz, at room temperature. Also wear behaviour of the alloy was studied against EN31 steel counter body, under dry sliding condition, at different loads from 2 to 10 kg and sliding velocity of 1 ms-1, at room temperature. The fretting fatigue life of the alloy was found to decrease drastically with increasing contact stress above 50 MPa. Wear rate of the alloy was found to increase linearly up to the entire load range investigated. Fall in fatigue life, with increase in contact load, occurs due to early crack initiation at stress concentration sites. These sites form due to combined effect of wearing in localized regions and consequent increase in absorption of oxygen in those regions because of much higher degree of plastic deformation in them. The wear behavior is discussed in terms of the nature of the debris formed. © 2013 The Authors.